Sages, Sympathy, and Suffering in Kant's Theory of Friendship. Issue 6 (August 2021) - Vilhauer, Benjamin
Abstract: Kant's theory of friendship is crucial in defending his ethics against the longstanding charge of emotional detachment. But his theory of friendship is vulnerable to this charge too: the Kantian sage can appear to reject sympathetic suffering when she cannot help a suffering friend. I argue that Kant is committed to the view that both sages and ordinary people must suffer in sympathy with friends even when they cannot help, because sympathy is necessary to fulfill the imperfect duty to adopt others' merely permissible ends (MPEs), and we ought to take friends' MPEs as our own. MPEs are individuated in terms of concepts which include marks of the first person, and no marks of law other than permissibility. To adopt ends of others individuated in terms of such concepts rather than merely promote them as means to different ends, those concepts must engage with one's feelings in a way that requires sympathy.